Application of potassium nitrate and salicylic acid improves grain yield and related traits by delaying leaf senescence in Gpc-B1 carrying advanced wheat genotypes - Tanin, Mohammad Jafar; Sharma, Achla; Ram, Hari; Singh, Satinder; Srivastava, Puja; Mavi, G. S.; Saini, Dinesh Kumar; Gudi, Santosh; Kumar, Pradeep; Goyal, Prinka; Sohu, V. S. (Frontiers in Plant Science, 2023)
Grain protein content (GPC) is an important quality trait that effectively modulates the end-use quality and nutritional characteristics of wheat flour-based food products. The Gpc-B1 gene is responsible for higher protein content in wheat grains. In addition to higher GPC, Gpc-B1 is generally associated with a reduced grain-filling period, which eventually causes a yield penalty in wheat. The main aim of the present study was to evaluate the effect of foliar application of potassium nitrate (PN) and salicylic acid (SA) on the physiological characteristics of a set of 12 genotypes, including nine isogenic wheat lines carrying the Gpc-B1 gene and three elite wheat varieties without the Gpc-B1 gene, grown in the experimental area of the Department of Plant Breeding and Genetics, PAU, Punjab, India. The PN application significantly increased the number of grains per spike (GPS) by 6.42 grains, number of days to maturity (DTM) by 1.03 days, 1000-grain weight (TGW) by 1.97 g and yield per plot (YPP) by 0.2 kg/plot. As a result of PN spray, the flag leaf chlorophyll content was significantly enhanced by 2.35 CCI at anthesis stage and by 1.96 CCI at 10 days after anthesis in all the tested genotypes. Furthermore, PN application also significantly increased the flag leaf nitrogen content by an average of 0.52% at the booting stage and by 0.35% at both anthesis and 10 days after anthesis in all the evaluated genotypes. In addition, the yellow peduncle color at 30 days after anthesis also increased by 19.08%, while the straw nitrogen content was improved by 0.17% in all genotypes. The preliminary experiment conducted using SA demonstrated a significant increase in DTM and other yield component traits. The DTM increased by an average of 2.31 days, GPS enhanced by approximately 3.17 grains, TGW improved by 1.13 g, and YPP increased by 0.21 kg/plot. Foliar application of PN or SA had no significant effect on GPC. The findings of the present study suggest that applications of PN and SA can effectively mitigate the yield penalty associated with the Gpc-B1 gene by extending the grain-filling period in wheat.